Enhancing Teaching and Learning Using GIS Technology Throughout UW System Campuses - Bajjali, William (My University, 2007)
Three broad-based activities will be implemented in order to improve the abilities of UW instructors to teach and provide relevant instructional activities using GIS technology. At least 48 faculty/staff from twelve disciplines of UW System will be involved in this project, with a potential of improving dozens of different classes that will affect over a thousand students. The objectives are to provide general and intermediate-level GIS knowledge and skills to UW instructors so that they can create exercises or laboratories in their own class environments. Create a user group of UW instructors as well as Wisconsin-based GIS professionals that can aid UW personnel in their GIS instructional problems and objectives. Provide curricula assistance to novice and intermediate GIS users within the UW-System who are developing new courses and programs.
Keywords: learning technology; GIS